“¿Qué nos dice el mapeo?” La generación de evidencia cultural a partir de la metodología de mapeo colectivo: Analizando las Cartografías Culturales de Lima, de Nodos Culturales - Elías Pineda, Natalia (2023)
Information generation, data processing and territorial approaches are keys to more accurate cultural and urban policies, whether at a community, private or public sphere. This article discusses the main findings from the cultural mapping project "Cultural Cartographies of Lima" (Nodos Culturales Association 2021) in order to spotlight alternative research methods for territory analysis that relies on cultural information such as type of infrastructure, cultural manifestations promoted, mobilizing agendas and audiences involvement. Information regarding the characteristics and distribution of Lima's cultural spaces tell us about urban inequalities and the civil resilience in the city that provides interesting evidence for the territory comprehension and policy making.